Optimization of the Dosage of Flucytosine in Combination with Amphotericin B for Disseminated Candidiasis: a Pharmacodynamic Rationale for Reduced Dosing - Hope, William W. (American Society for Microbiology, 2007)
Amphotericin B and flucytosine (5FC) have an additive effect when used for disseminated candidiasis. Here, we bridge the results of an experimental pharmacodynamic study to humans and demonstrate that a 5FC dosage of 25 mg/kg of body weight/day in four divided doses in combination with amphotericin B produces near-maximal effect.